The cicada genus Macrosemia Kato, 1925 (Hemiptera: Cicadidae) from Vietnam, with the description of a new species and key to species - Thai, Pham Hong; Hong, Bui Minh; Constant, Jerome (Academia Journal of Biology, 2016)
The species of the genus Macrosemia from Vietnam are taxonomically reviewed. One species of cicada is described, Macrosemia lamdongensis from Lam Dong province in Tay Nguyen area, Vietnam. Two species, Macrosemia assamensis (Distant, 1905) and Macrosemia divergens (Distant, 1917), are removed from the Vietnam cicada fauna. Information on the distribution of all known species is given. Photos of the adult, illustrations of the male genitalia and a distribution map are provided for the new species. A key to the species of Macrosemia based on characters of the male adults is also given.